2002
DOI: 10.1034/j.1600-0668.2002.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective perceptions, symptom intensity and performance: a comparison of two independent studies, both changing similarly the pollution load in an office

Abstract: The present paper shows that introducing or removing the same pollution source in an office in two independent investigations, one in Denmark and one in Sweden, using similar experimental methodology, resulted in similar and repeatable effects on subjective assessments of perceived air quality, intensity of sick building syndrome symptoms and performance of office work. Removing the pollution source improved the perceived air quality, decreased the perceived dryness of air and the severity of headaches, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 7 publications
1
45
0
1
Order By: Relevance
“…This field therefore represents a massive gross energy saving potential. Simply reducing ventilation rates, however, will deteriorate the indoor air quality and therefore sort unwanted effects such as increasing the incidence of respiratory illness (Seppänen & Fisk, 2004) and loss of productivity (Wargocki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This field therefore represents a massive gross energy saving potential. Simply reducing ventilation rates, however, will deteriorate the indoor air quality and therefore sort unwanted effects such as increasing the incidence of respiratory illness (Seppänen & Fisk, 2004) and loss of productivity (Wargocki, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There are many self-reported triggers including weather, [1] fatigue, stress, food, menstruation, and infections [2]. Air quality in the home [3], office environment [4,5], and the occupational setting [6] may also exacerbate headaches. A daily diary study of 32 headache sufferers in Italy revealed that the severity and frequency of headaches was related to days with higher concentrations of carbon-monoxide and nitrogen dioxide [7].…”
Section: Introductionmentioning
confidence: 99%
“…Migraine triggers include weather [1], fatigue, stress, food, menstruation, and infections [2]. Air quality in the home [3], office environment [4,5], and occupational setting may play a role in the exacerbations of migraine headache [6]. A daily diary study of 32 headache sufferers in Italy revealed that the severity and frequency of headaches correlated with days when elevated concentrations of carbon monoxide and nitrogen dioxide were recorded [7].…”
Section: Introductionmentioning
confidence: 99%